The General Allocation Fund (DAU) Formulation Policy: Incentives or Disincentives to the Fiscal Independence of Local Governments - Haribowo, Kun; Wihastuti, Latri (Jurnal Ekonomi Kuantitatif Terapan; 2022: Vol. 15, No. 1, Februari 2022 (pp.1-161), 2022)
The implementation of fiscal decentralization in Indonesia is expected to improve economic welfare for the people in the regions because it can bring the government closer to the community in providing public services according to people's preferences. As a consequence of decentralization, the central government provides transfer funds to local governments. The amount of transfer funds to local governments is around thirty percent of total National Budget (APBN), excluding central expenditure funds allocated to regions. Central government expect the fiscal dependence of local governments to be reduced. In fact, since regional autonomy was implemented in 2001 until 20 years later, regional independence has never been achieved. Ratio of local revenues (Pendapatan Asli Daerah,PAD) to total revenues in Regional Budget (APBD) ranged from 36.8 percent in Java to only 6.1 percent in Maluku and Papua., the rest still expects transfer funds from the central government. It is suspected that regional independence is closely related to the formulation of the General Allocation Fund (Dana Alokasi Umum, DAU) where PAD is a component of reducing DAU in the formulation. It can be seen from this formulation that the central government has ambiguous policies. On the one hand, it punishes local governments whose PAD efforts are high by providing a smaller DAU, but on the other hand they hope that the regional fiscal dependence will be decrease through an increase in PAD. When there is a view that the effort to collect local taxes is not an important factor for the regions, the regions will prefer to receive a higher DAU rather than increasing their tax collection effort but reducing the DAU. This study will try to analyze the efforts of local governments and will examine the data on variables related to the DAU whether it is consistent with its formulation. Through Weight Least Square (WLS) analysis which is more suitable for heteroscedasticity data that may arise from the diversity of data between regions, this study will see whether the DAU formulation becomes an incentive or disincentive for regional fiscal independence through increasing PAD. The results showed that the PAD variable had a negative relationship with DAU. This means that the DAU formula actually becomes a disincentive for regions to increase their PAD. The greater the PAD, the smaller the DAU received by the local government. Review this policies or reformulate the DAU formulation in accordance with the principles of local government fiscal independence need to be implemented immediately.